2020
DOI: 10.1108/bfj-02-2020-0138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a documentary on consumer perception of the environmental impact of meat consumption

Abstract: PurposeMeat consumption causes a large amount of global greenhouse gas emissions and other environmental problems. Studies showed that consumers underestimate the environmental impact of meat consumption compared to other food-related behaviours. A video intervention was conducted to investigate the effect of information on consumers' perception and behaviour.Design/methodology/approachTwo didactically different videos about meat and the environment and a control video were shown to 189 participants. Ratings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…It has been argued that people in higher-income, developed countries tend to prioritise environmental protection in meat choices more than citizens in emerging economies (Franzen and Vogl, 2013;Tucker, 2018;Cheah et al, 2020). Hence, providing information to consumers on the environmental benefits of eating less meat may influence behavioural Sustainable meat consumption intentions intentions (Bschaden et al, 2020). However, scholars argue that only a minority of the population express concern regarding meat (Sanchez-Sabate and Sabat e, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that people in higher-income, developed countries tend to prioritise environmental protection in meat choices more than citizens in emerging economies (Franzen and Vogl, 2013;Tucker, 2018;Cheah et al, 2020). Hence, providing information to consumers on the environmental benefits of eating less meat may influence behavioural Sustainable meat consumption intentions intentions (Bschaden et al, 2020). However, scholars argue that only a minority of the population express concern regarding meat (Sanchez-Sabate and Sabat e, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The production and consumption of meat are associated with negative externalities (Bonnet et al, 2020). Livestock farming disproportionally affects climate change and exploits land, water and energy resources much more than the cultivation of plant-based foods (Mogensen et al, 2020;Sahakian et al, 2020;Bschaden et al, 2020). Excessive meat consumption also poses health risks such as cardiovascular disease, stroke and forms of cancer (Cliceri et al, 2018;de Boer et al, 2017;Apostolidis and McLeay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, consumers are exposed to many forms of video-based communications. However, research on the effect of videos as a communication medium remains limited [ 2 ]. This dataset contributes to understanding the potential impact of video-based communication strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Forum 2023, 26, 36 2 of 6 Besides contextual effects, effects of top-down information (i.e., videos) on food-related behavior have been reported as well. For instance, Bschaden et al [8] used videos to inform people about the impact of sustainable dietary behavior and showed that this information can affect consumers' perception in the desired direction. In another study using video clips as goal-priming stimuli, direct priming of a health goal proved to be effective in steering consumers towards healthier food options [9].…”
Section: Introductionmentioning
confidence: 99%